Analisis kebutuhan bahan ajar fisika ditinjau dari kompleksitas proses kognitif menurut taksonomi Bloom revisi pada materi hukum newton tentang gerak di SMAN kota Padang - Santi Asmara; Amali putra (Universitas Negeri Padang, 2020)
One of the characteristics of learning materials in secondary schools in accordance with the 2013 curriculum is referring to the Revised Bloom Taxonomy, in the form of 6 levels of cognitive processes. The issues that are the focus of this discussion are: Do the main teaching materials used in high school physics lessons in Padang meet these requirements? This research is a descriptive study with an explorative approach, in which this study provides a report on the object under study in accordance with the facts found and is associated with 6 levels of cognitive processes according to Bloom's revised taxonomy on teaching materials for class X Semester 2 used in physics learning High school in Padang. Data processing is done by percentage techniques. The results showed that in studying Newton's laws of motion material in the city of Padang: a) the proportion of the average percentage of the level of cognitive processes that were trained in teaching materials for each ability level was; considering 7.03%, understanding 7.03%, applying 57.40%, analyzing 20.07%, evaluating 0% and creating 0%. b) the proportion of the average percentage of implementation of the scientific approach trained in teaching materials for each level are: observing 13%, asking 15%, gathering information 8%, reasoning 0%, communicating 7%. This study concludes that the results of the analysis of basic teaching materials used in public high schools in Padang a) have not trained all levels of cognitive processes mandated by the revised Bloom taxonomy. b) scientific approach in teaching materials has not been fully implemented properly. c) the characteristics of teaching materials needed for physics learning are teaching materials that are able to: develop students' reasoning abilities; and oriented towards achieving HOTS.